Consequences of insecticide overuse in Hungary: assessment of pyrethroid resistance in Culex pipiens and Aedes albopictus mosquitoes - Rebeka Csiba; Zsaklin Varga; Dorina Pásztor; Bianka Süle; Vera Ihuoma Ogoke Mxinwa; Zoltán Soltész; Brigitta Zana; Krisztián Bányai; Gábor Kemenesi; Kornélia Kurucz (Parasites & Vectors)
Abstract Background Mosquitoes, as vectors of various pathogens, have been a public health risk for centuries. Human activities such as international travel and trade, along with climate change, have facilitated the spread of invasive mosquitoes and novel pathogens across Europe, increasing the risk of mosquito-borne disease introduction and their spread. Despite this threat, mosquito control in Hungary still relies predominantly on chemical treatments, which poses the risk of developing insecticide resistance in local populations. While pyrethroid resistance has been documented in several countries, there is no information on this issue from Hungary. This study aims to investigate the presence of resistance in Hungarian mosquito populations by analyzing a native, already known disease vector and a recently established invasive species with public health significance. Methods We assessed the presence of knockdown resistance (kdr) mutations L1014F in Culex pipiens and V1016G and F1534C in Aedes albopictus mosquitoes, which are responsible for pyrethroid resistance. Mosquito specimens were investigated retrospectively, collected from previous years within the framework of local monitoring programs run in urban areas representing five regions of Hungary. The mutations in mosquitoes were detected individually by allele-specific polymerase chain reaction (PCR) and gel electrophoresis, following generally used protocols. Results In Cx. pipiens, the kdr mutation was detected across all five collection sites, with resistance allele frequencies ranging from 18.1% to 36.3%. Resistance alleles were identified in homozygosity and heterozygosity with the susceptible allele, resulting in 53% of the investigated mosquitoes showing resistance to pyrethroids in the Hungarian populations. In contrast, for Ae. albopictus, the analyzed individuals were found to carry only the susceptible alleles, indicating a homozygous susceptible genotype across the investigated populations on the basis of V1016G and F1534C genes. Conclusions Our work highlights the consequences of the unilateral and long-term use of chemical treatments on mosquitoes. This indicates an urgent need for a change of concept in mosquito control strategy in Hungary, as well as in countries where mosquito control still relies dominantly on insecticides. The restricted use of chemical treatment is highly recommended to prevent the development of pyrethroid resistance in recently established populations of the invasive Ae. albopictus, and to decrease the public health risk of vector-borne diseases. Graphical Abstract